Welding Training for Youth Organization in Dayeuh Village - Asep Saepudin; Hilman Sholih; Wisnu Pracoyo; Asep Dharmanto; W. Wilarso (Jurnal Dedikasi, 2020)
During quite a high job competition, each individual must improve their abilities in various fields of science and skills. Development of human resources to improve product quality and selling value. Human Resources (HR) that are not supported by soft skills and hard skills will reduce the ability to work, of course, needed by young people with a higher desire to improve hard skills and soft skills. This welding training, one of the STTMC programs aimed at improving the quality of young people in STTMC and surrounding areas. Whereas in the industrial environment increasing human resources to compete in labor competition. In building good relationships between universities and communities around the industry.  Also, we can equip young people with the skills needed in the fields of welding, entrepreneurship, industry, and the world of projects. Where the majority of the world of work requires smart people and have the ability in the field of hard skills. Through this training, it can help the difficulties of young people in the field of welding in the industrial world and efforts to improve the ability of the field of welding skills by collaboration between STTMC and PT. CG Power Indonesia.